Comparative plasma exposure of albendazole after administration of rapid disintegrating tablets in dogs - Castro, Silvina Gabriela (2013)
The main objectives of this study were (a) to evaluate the in vitro performance of the rapid disintegration tablets as a way to improve the solid dispersions and (b) to study the in vivo pharmacokinetics of the albendazole modified formulation in dogs. Rapid disintegration of tablets seems to be a key factor for efficiency of solid dispersions with regard to improvement of the albendazole bioavailability. The in vivo assays performed on dogs showed a marked increase in drug plasma exposure when albendazole was given in solid dispersions incorporated into rapid disintegration tablets compared with conventional solid dosage form.